Unusual substitutions in HIV-1 vif from children infected perinatally without progression to AIDS for more than 8 years without therapy - de Maio, Federico Andres (2012)
The HIV-1 vif gene encodes for an accessory protein that is central for virus replication due mainly to its capacity to counteract the antiviral action of host APOBEC3 restriction factors. In order to evaluate whether HIV-1 vif alterations account for a delayed progression to AIDS in children infected perinatally, the vif genes from a group of 11 patients who exhibited an extremely slow disease progression (slow progressors) were studied by direct sequencing. In addition, the vif genes from a group of 93 children with typical disease progression (typical progressors) were analyzed for comparison. Phylogenetic analysis indicated that sequences from slow progressors did not have a common origin, discarding a shared ancestor of reduced virulence. There were no differences in the diversity between the vif genes from slow and typical progressors. No gross defects showing a clear distinction among sequences from both groups of children were found. However, in the deduced Vif proteins, changes V13I, V55T, and L81M were observed only in sequences from slow progressors. By analyzing sequences stored in databases, these mutations were determined as unusual substitutions occurring at highly conserved Vif sites across different HIV-1 clades, but were observed with an increased frequency in sequences from elite controllers. These mutations were in the Vif regions reported as relevant for protein activity. These findings suggest that the Vif sequences from slow progressors carry unusual substitutions, which may alter the protein function and may contribute to viral attenuation.